Exploring the relationship between employee engagement and counterproductive work behaviour - Mvuyana, Sphindile; Nzimakwe, Thokozani Ian; Utete, Reward (Frontiers in Psychology, 2025)
The purpose of the study was to explore the relationship between employee engagement and counterproductive work behaviours of employees at the leading university in South Africa. The study employed qualitative approach and structured interviews were used to gather data from the both academic and professional services staff. The collected data from fifteen (15) respondents were analysed using thematic analysis, leading to the identification of key themes and patterns. Based on the findings, it became evident that there is an inverse relationship between employee engagement and counterproductive work behaviour. The study also revealed lack of an effective probationary period, unequal treatment of academic and professional services staff in terms of retention strategies, and insufficient attention given to employee engagement were among the primary factors contributing to disengagement within the institution. The study concluded that there is a pressing need for change and the implementation of new systems to enhance employee engagement at the organisation.